PENGARUH CO-FIRING SERBUK KAYU KEDONDONG TERHADAP PERFORMA DAN EMISI GAS BUANG BRIKET BATU BARA - Nuryanto, Edi; Sudarno, Sudarno; Winardi, Yoyok (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Coal is the main fuel in steam power plants (PLTU) whose availability is dwindling. Realizing this, one of the efforts made is to mix coal with other fuels, known as Co-Firing. This is done as an effort to substitute new and renewable energy and is friendly to the environment. The purpose of this study was to find out the effect of a mixture of kedondong sawdust in coal on performance and exhaust emissions at PLTU. This research was conducted using quantitative methods based on experimental data. Kedondong wood powder as co-firing is varied, namely 5%, 10%, 15%, 20% and compared to 100% coal. The combustion process is carried out in the boiler and the data obtained is in the form of operating parameters and exhaust emissions. Based on this research, it was found that all operational parameter data were normal and were within the allowable standard limits. Likewise, exhaust emissions produced by both NOx and SO2 show better results than the use of 100% coal.